1962
DOI: 10.1017/s0022029900010955
|View full text |Cite
|
Sign up to set email alerts
|

The reactivation of milk alkaline phosphatase after heat treatment

Abstract: A simple system was developed, consisting of a solution of jS-glycerophosphate, jS-lactoglobulin and magnesium ions, in which alkaline phosphatase isolated from milk became strongly reactivated following heat treatment for 45 sec in boiling water. From 10 to 30% of the original enzyme activity reappeared after incubation at 37 °C. Variations in the components of the system, and factors affecting it, were studied. Salts of Hg, Zn and Cd inhibited reactivation at low concentrations.Milk which, after the same hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

1970
1970
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…A number of attempts have been made to explain the mechanism of reactivation of AlP (see Andrews et al, 1992;Copius Peereboom, 1970;Fox, 2003;Fox & Morrissey, 1981;Fox et al, 2003;Kresheck & Harper, 1967;Linden, 1979;Lyster & Aschaffenburg, 1962;Murthy, Cox, & Kaylor, 1976;Shakeel-ur-Rehman et al, 2003). There is evidence that the form of the enzyme that becomes reactivated is membrane-bound and several factors which influence reactivation have been established.…”
Section: Reactivation Of Alkaline Phosphatasementioning
confidence: 99%
“…A number of attempts have been made to explain the mechanism of reactivation of AlP (see Andrews et al, 1992;Copius Peereboom, 1970;Fox, 2003;Fox & Morrissey, 1981;Fox et al, 2003;Kresheck & Harper, 1967;Linden, 1979;Lyster & Aschaffenburg, 1962;Murthy, Cox, & Kaylor, 1976;Shakeel-ur-Rehman et al, 2003). There is evidence that the form of the enzyme that becomes reactivated is membrane-bound and several factors which influence reactivation have been established.…”
Section: Reactivation Of Alkaline Phosphatasementioning
confidence: 99%
“…showed that reactivation did not take place on storage at lOoe or less, but that at temperatures above 20 0 e reactivation was considerable, and was complete after about 14 days. Lyster & Aschaffenburg (1962) examined the phenomenon, and postulated that the activity of alkaline phosphatase was determined by the combined effects of an inhibitor and an activator, both being heat labile but with different kinetics.…”
Section: Enzyme Inactivationmentioning
confidence: 99%
“…All samples with an alkaline phosphatase activity of greater than 100 mU L À1 were retested to confirm the result and, in addition, were tested for bacterial phosphatase (Knight & Fryer, 1989;BS ISO 11816-1, 1997) and reactivation of phosphatase enzyme (Lyster & Aschaffenburg, 1962;AOAC, 1995, Chapter 33). If either bacterial phosphatase or reactivation were detected in samples the sample results were excluded.…”
Section: Fluorimetric Test For Bovine Alkaline Phosphatasementioning
confidence: 99%